2009
DOI: 10.1159/000192799
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Demineralization and Dentin Reactions in Radiation-Related Caries

Abstract: Radiation-related caries is a unique form of rampant decay and is a complication of head and neck radiotherapy that frequently causes generalized dental destruction and impairs quality of life in cancer patients. The aim of this study was to investigate the patterns of demineralization of caries in irradiated patients and to establish whether direct radiogenic damage to the dentition might be important in the progression of radiation-related caries. Teeth from patients who had concluded radiotherapy were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
89
0
33

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 38 publications
12
89
0
33
Order By: Relevance
“…However, oral cancer patients exposed to radiotherapy demonstrate post-radiation dental lesions that initiate with enamel shear fracture that can result in partial to total enamel delamination, suggesting DEJ instability (Jongebloed et al, 1988;Pioch et al, 1992;Jansma et al, 1993). While postradiotherapy dentition breakdown has been linked to radiation-induced salivary gland damage (Vissink et al, 2003a;Kielbassa et al, 2006;Silva et al, 2009), our group completed a clinical study and reported a significant correlation between pathologic enamel loss and individual tooth-level radiation dose in oral cancer patients (Walker et al, 2011). Three tiers of tooth response were observed: at < 30 Gray (Gy), minimal tooth damage occurred; between 30 and 60 Gy, there was a 2 to 3x increased risk of tooth breakdown (salivary gland impact); and at > 60 Gy, there was a 10x increased risk of tooth damage, indicating radiation-induced damage to the tooth in addition to salivary gland damage.…”
mentioning
confidence: 99%
“…However, oral cancer patients exposed to radiotherapy demonstrate post-radiation dental lesions that initiate with enamel shear fracture that can result in partial to total enamel delamination, suggesting DEJ instability (Jongebloed et al, 1988;Pioch et al, 1992;Jansma et al, 1993). While postradiotherapy dentition breakdown has been linked to radiation-induced salivary gland damage (Vissink et al, 2003a;Kielbassa et al, 2006;Silva et al, 2009), our group completed a clinical study and reported a significant correlation between pathologic enamel loss and individual tooth-level radiation dose in oral cancer patients (Walker et al, 2011). Three tiers of tooth response were observed: at < 30 Gray (Gy), minimal tooth damage occurred; between 30 and 60 Gy, there was a 2 to 3x increased risk of tooth breakdown (salivary gland impact); and at > 60 Gy, there was a 10x increased risk of tooth damage, indicating radiation-induced damage to the tooth in addition to salivary gland damage.…”
mentioning
confidence: 99%
“…1,2 Although the exact nature of RRC has not been completely understood, it can be considered as a complex and multifactorial disease related to the direct and indirect effects of radiation on the salivary glands and teeth. [3][4][5][6][7][8] Despite recent advances in radiation therapy and implementation of multidisciplinary approaches, the oral environment of patients who undergo head and neck therapy still poses a clinical challenge for dentistry. Therefore, a better understanding of carious development in patients with cancer could be useful for the improvement of clinical management.…”
mentioning
confidence: 99%
“…3 Optical coherence tomography (OCT) is a nondestructive imaging technique using low-coherence interferometry to determine the time delay and magnitude of backscattered light reflected off a transparent and semitransparent structure. 9 By using the optical properties of reflection and scattering into sound and carious mineralized tissues, it is possible to evaluate and characterize morphological structures as the CEJ and DEJ.…”
mentioning
confidence: 99%
“…This phenomenon could be caused by the fact that patients affected by radiation-related caries do not present dental pain on a routine basis. Several hypotheses suggest that the direct effects of radiation on the dental pulp would be able to negatively affect the metabolism of odontoblasts and compromise the response of the dentin-pulp complex to the progression of radiation related caries, explaining the absence of pain even in deep carious lesions (3,11). However, other studies do not support direct radiation damage to the innervation of the pulp that would be able to negatively affect the viability of odontoblasts, the repair capacity of dentin against caries progression, and the inhibition of pulp sensitivity and responses to caries progression (10,12,13).…”
Section: Discussion:-mentioning
confidence: 99%